tan23°+tan37°+√(3)tan23°*tan37°

来源:学生作业帮助网 编辑:作业帮 时间:2018/12/13 23:58:51
tan23°+tan37°+√(3)tan23°*tan37°tan23°+tan37°+√(3)tan23°*tan37°tan23°+tan37°+√(3)tan23°*tan37°tan60=√

tan23°+tan37°+√(3)tan23°*tan37°
tan23°+tan37°+√(3)tan23°*tan37°

tan23°+tan37°+√(3)tan23°*tan37°
tan60=√3 =(tan23+tan37)除以(1-tan23*tan37)(tan的和角公式)
tan23+tan37=√3 (1-tan23*tan37)
tan23°+tan37°+√(3)tan23°*tan37°
=√3 (1-tan23*tan37)+√(3)tan23°*tan37°
=√3 -√3tan23*tan37+√(3)tan23°*tan37
=√3

tan60=(tan23+tan37)/(1-tan23*tan37)
tan23+tan37=tan60tan23*tan37
tan23+tan37+√(3)tan23*tan37=√(3)

tan60°=tan(23°+37°)
=(tan23°+tan37°)/(1-tan23°*tan37°)
等式两边同乘(1-tan23°*tan37°)
即tan60°(1-tan23°*tan37°)=tan23°+tan37°
即tan23°+tan37°=tan60°-tan60°tan23°*tan37°
tan23°+tan37°...

全部展开

tan60°=tan(23°+37°)
=(tan23°+tan37°)/(1-tan23°*tan37°)
等式两边同乘(1-tan23°*tan37°)
即tan60°(1-tan23°*tan37°)=tan23°+tan37°
即tan23°+tan37°=tan60°-tan60°tan23°*tan37°
tan23°+tan37°+tan60°tan23°*tan37°=tan60°
又tan60°=√3
即tan23°+tan37°+√(3)tan23°*tan37° =√3

收起